The impact of livestock improvement on the South African economy : a policy analysis using a dynamic computable general equilibrium model - Tyelo, Mkhanyisi (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.